SWOT ANALYSIS AS A STRATEGY TO INCREASE THE COMPETITIVENESS OF MSMES - Sumarni, Mutia (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2022)
SWOT ANALYSIS AS A STRATEGY TO INCREASE THE COMPETITIVENESS OF MSMES Abstract Purpose: This study aims to assess the application of SWOT analysis as a strategic approach to enhance the competitiveness of street vendors in Langsa City. Design/methodology/approach: The research employs a descriptive qualitative method, drawing from primary data gathered through observation, interviews, and documentation. The study uses purposive sampling, selecting four Fried Chicken Street Vendors in Langsa City based on characteristics such as extensive production experience and strategically located sales points. The SWOT analytical method is utilized to examine internal and external factors affecting the vendors. Findings: The results reveal internal factor matrix values of 2.92 and external factor matrix values of 3.14. The Fried Chicken businesses in Langsa City fall into the growth category, indicating a period of growth in sales, asset profit, or a combination of the two. The Cartesian diagram places these businesses in quadrant I, suggesting an aggressive strategy. Research limitations/implications: The research is limited to Fried Chicken Street Vendors in Langsa City and may not generalize to other types of street vendors or locations. The findings emphasize the importance of adapting strategies to external opportunities and threats while leveraging internal strengths. Practical implications: Understanding the SWOT analysis results allows street vendors in Langsa City to formulate strategic plans that capitalize on their strengths, address weaknesses, seize opportunities, and mitigate threats. This can enhance their competitiveness in the market. Keywords: Street Vendors, Competitiveness, Strategy ANALISIS SWOT SEBAGAI STRATEGI MENINGKATKAN DAYA SAING UMKM Abstrak Tujuan: Penelitian ini bertujuan untuk mengkaji penerapan analisis SWOT sebagai pendekatan strategis untuk meningkatkan daya saing PKL di Kota Langsa. Desain / metodologi / pendekatan: Penelitian ini menggunakan metode kualitatif deskriptif, menggambar dari data primer yang dikumpulkan melalui observasi, wawancara, dan dokumentasi. Penelitian ini menggunakan purposive sampling, memilih empat Pedagang Kaki Lima Ayam Goreng di Kota Langsa berdasarkan karakteristik seperti pengalaman produksi yang luas dan titik penjualan yang strategis. Metode analisis SWOT digunakan untuk memeriksa faktor internal dan eksternal yang mempengaruhi vendor. Temuan: Hasil penelitian menunjukkan nilai matriks faktor internal sebesar 2,92 dan nilai matriks faktor eksternal sebesar 3,14. Bisnis Ayam Goreng di Kota Langsa masuk dalam kategori pertumbuhan, menunjukkan periode pertumbuhan penjualan, laba aset, atau kombinasi keduanya. Diagram Cartesian menempatkan bisnis-bisnis ini di kuadran I, menunjukkan strategi agresif. Keterbatasan / implikasi penelitian: Penelitian ini terbatas pada Pedagang Kaki Lima Ayam Goreng di Kota Langsa dan tidak boleh menyamaratakan jenis pedagang kaki lima atau lokasi lainnya. Temuan ini menekankan pentingnya mengadaptasi strategi terhadap peluang dan ancaman eksternal sambil memanfaatkan kekuatan internal. Implikasi praktis: Memahami hasil analisis SWOT memungkinkan pedagang kaki lima di Kota Langsa untuk merumuskan rencana strategis yang memanfaatkan kekuatan mereka, mengatasi kelemahan, menangkap peluang, dan mengurangi ancaman. Ini dapat meningkatkan daya saing mereka di pasar. Kata kunci: Pedagang Kaki Lima, Daya Saing, Strategi